Delineation of geographic markets for fed cattle - Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1997)
Determining the extent of geographic markets for fed cattle is important for monitoring performance of the industry. The ability of packing plants to influence prices is determined in part by their ability to segment the market for fed cattle and isolate themselves from plants in other regions. This study analyzed transaction data from 43 U.S. steer and heifer slaughter plants collected by the Grain Inspection Packers and Stockyards Program for approximately a 1-year period during 1992-93. Beef packers procured an average of 64% of their cattle within 75 miles of packing plants, 82 % within 150 miles, and 92% within 250 miles. However, these average distances varied by region of the U.S. Prices were linked strongly across plants, suggesting a national market for fed cattle. This indicates that local measures of packing plant concentration overstate the degree of concentration among potential cattle buyers in the region.
Keywords: Cattlemen' s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Geographic markets for cattle; Beef packers; Packer concentration